Mitigating the negative effects of emotional labor: A study of disaster response and recovery workers after the 2010 Haiti earthquake. Issue 1 (8th January 2020) - Kroll, Alexander; Remington, Christa L.; Awasthi, Pallavi; Ganapati, N. Emel
Abstract: One of the most pressing governance challenges around the globe is managing disasters and their underlying risk factors. Little is known about effective strategies to minimize burnout and posttraumatic stress disorder among practitioners involved in addressing this challenge, especially in countries that rely mainly on international aid agencies for the delivery of basic services to their citizens. This article draws on the emotional labor literature to identify routes addressing the negative consequences of doing response and recovery work in postdisaster contexts. Based primarily on surveys and interviews with response and recovery workers involved after the 2010 Haiti earthquake, it advances and extends previous emotional labor theory on the mitigating factors of service workers' burnout. It points to the importance of autonomy and training as well as five coping mechanisms: relying on informal support, utilizing humor, leaving work at work, decompressing alone, and rotating job positions.